MUSHARAKAH MUTANAQISAH (MM) HOME FINANCING FOR AFFORDABILITY OF HOMEOWNERSHIP: A SIMULATION CASE STUDY APPROACH - Hock Eam, Lim; Mohd Yusof, Rosylin; Mohd Khan, Shazida Jan (PLANNING MALAYSIA, 2019)
Since 1990s, the increase in housing price, housing loan application rejection and bankruptcy due to housing loan default, have highlighted the need for a better way of home financing. Islamic home financing that promotes social well-being is a suitable alternative. Malaysia is in the forefront of Islamic financing system development, and Islamic home financing including the Musharakah Mutanaqisah (MM) is being implemented. Nevertheless, the MM is implemented with Wa’d. This jeopardizes the true spirit of partnership in MM home financing. Why MM is implemented with Wa’d? Is MM without Wa’d not feasible? The main objective of the present study is to simulate the case of MM without Wa’d and evaluate its feasibility. Results revealed that it is feasible to implement MM without Wa’d. In addition, MM without Wa’d could reduce the probability of loan default and increases the affordability of homeownership